Outbound Training Based on Local Wisdom and Art Attractions in Gamplong Tourism Village - Nuvriasari, Audita; Harsoyo, Titik Desi; Rozi, Anief Fauzan (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this community service activity is to develop tourist attractions based on local wisdom so that they can be used as one of the tourist attractions. The obstacles faced by Pokdarwis are the limitations in developing outbound training materials based on local wisdom and cultural potential in the form of dance arts that have not been explored as tour packages that can be offered to visitors. The program implemented is Outbound Training based on local wisdom aimed at outbound guides and modern-traditional creative dance training. The activity method is delivered through counseling and training where partners and the community participate directly in the activity. The results of the activity are increased knowledge and skills of partners in packaging outbound materials and games based on local wisdom.